Giving and religiosity: A portuguese point of view - Abreu, M. E.; Laureano, Raul M. S.; Vinhas da Silva, Rui (Third Symposium on Ethichs and Social Responsibility Research, 2015)
This paper discusses the driving mechanisms of religiosity in terms of donations practices, and donor choice in giving either to religious organizations or secular organizations in Portugal. As a matter of fact, donations practices are a topic of high relevance in the marketing literature today, mainly due to its implicit links to fundraising research and activities. Based on a survey of Portuguese nonprofit organizations, 612 donors reported their preferences when giving. Being religious affiliated, and displaying a high level of religiosity has been identified as a determinant of donate regularly and giving high amounts. Moreover, donor choice in giving either to religious organizations or secular organizations has been found to be an important factor for secular people, whereas religious people tend to give to any kind of organization. Finally, the findings of this study are useful for marketers in nonprofit organizations who want to attract and retain donors and, like this, do contribute to the sustainability of the organizations.